Eastern Caribbean Currency Union : 2017 Discussion on Common Policies of Member Countries-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses key points of 2017 Discussions on Common Policies of Member Countries of the Eastern Caribbean Currency Union (ECCU). Favorable external conditions continue to support economic recovery in the ECCU, but flat tourism receipts and falling revenues from citizenship programs have weakened growth. The fiscal position has deteriorated slightly, and public debt remains high. Despite progress on financial sector reform, bank lending continues to decline while indigenous banks' profitability is adversely impacted by increasing costs to secure correspondent banking relationships. The short-term outlook is favorable and risks are broadly balanced, but strong structural policies are needed to address impediments to medium-term growth.